Local Wisdom of the Aceh Jaya Society in terms of Indigenous Cuisine that can be learned in Chemistry Learning in Schools - Ria Ervilita; Ainun Mardhiah (Universitas Serambi Mekkah, 2022)
This study aims to determine the local wisdom of the people of Aceh Jaya in terms of the indigenous cuisine of the society that can be included in learning chemistry at the school. Local wisdom is a way of living a wise life that is passed down from generation to generation through oral traditions, proverbs, or folklore. Indigenous specialties are dishes that are often or commonly consumed in an area with characters that usually reflect the character of the society and have certain local identity and characteristics. The sample in this study is the people of Aceh Jaya which is divided into three (3) districts, namely the eastern district which is in the mountainous area, the western district which is on the outskirts of the sea, and the northern district which is on the edge of the highway. The sampling technique used was the purposive sampling technique. Data collection techniques used are observations of activities carried out by society, interviews with society leaders, and documents. The data collection instruments are in the form of observation sheets, interview sheets, and document reviews. Furthermore, the research data were analyzed using the Miles and Huberman model, namely the stages of data reduction, data presentation, and conclusion. The results of the study show that the indigenous dishes of the Aceh Jaya people that are still being preserved include jruek drien (tempuyak durian), jruek kuini (tempuyak kuini), gule jruk engkot kerling (curry sour fish), Plik u, peuleumak oun murong ngon boh drien putik (coconout milk soup uses moringa leaves and young durian), peulemak or tumis daun pakis (coconut milk / sauteed fern leaves), daun pakis tekerabe (urap pakis). This research concludes that the typical cuisine of the Aceh Jaya society is the local wisdom of the society that can be included in learning chemistry, the chemical processes obtained in indigenous community dishes are the fermentation process, the mixture of substances, separation of mixtures, acids and bases, solutions and colloids. The chemical constituents found in these typical dishes are vitamins A and C, glucose, protein, fat, nutrition, calcium, phosphorus, iron, minerals, carotenoids, polyphenols, flavonoids, alkaloids, tannins, saponins, and oxalates. Keywords: Local Wisdom, Indigenous Cuisine, Chemistry Learning, and Chemical Compositions.